2020
DOI: 10.3390/jcs4020045
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Thaw Performance Characterization and Leachability of Potassium-Based Geopolymer Concrete

Abstract: It is well known that concrete is one of the most widely used construction materials in the world, and cement as its key constituent is partly responsible for global Carbon Dioxide (CO2) emission. Due to these reasons, high strength concrete with lower CO2 emission, and concrete with lower reliance on natural resources is increasingly popular. Geopolymer Concrete (GPC), due to its capability to minimize the consumption of natural resources, has attracted the attention of researchers. In cold regions, frost act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…This agrees with former authors: Bakharev et al [20], following experiments with sodium sulfate solutions, found strength increase in AAS concrete. Similarly, Luga [29] evidenced that slag geopolymers increased compressive strength by 14-24% respectively following wet-dry cycles, and other authors found a compressive strength increase after freeze-thaw cycling [32][33]35]. The strength increase can be attributed to the presence of smaller pores [34] but is is likely the result of continuing hydration [20].…”
Section: Effect Of Accelerated Weathering On the Mechanical Strength Of Aas Materialsmentioning
confidence: 92%
See 1 more Smart Citation
“…This agrees with former authors: Bakharev et al [20], following experiments with sodium sulfate solutions, found strength increase in AAS concrete. Similarly, Luga [29] evidenced that slag geopolymers increased compressive strength by 14-24% respectively following wet-dry cycles, and other authors found a compressive strength increase after freeze-thaw cycling [32][33]35]. The strength increase can be attributed to the presence of smaller pores [34] but is is likely the result of continuing hydration [20].…”
Section: Effect Of Accelerated Weathering On the Mechanical Strength Of Aas Materialsmentioning
confidence: 92%
“…Fu et al [31] evidenced weight loss under 1% a frost resistance coefficient of ∼90% after 300 cycles. It is also relatively common to find instances of strength increase following durability cycling in the literature [32][33][34][35].…”
Section: Sio2mentioning
confidence: 99%
“…Internal microcracks are formed as a result of the expansion pressure. An increase in freeze–thaw cycles contributes to the extension of micro-cracks over time [ 29 ]. There are very limited investigations on the performance of geopolymer concrete and SCGC under freeze–thaw tests, and studies in this field need to be extended.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, there are some studies that show the results of incorporating EAFD in processes of geopolymerization of coal fly ash [16,17,37]. On the other hand, it should be noted that there is a significant number of published studies that evaluate the environmental implications of geopolymeric systems based on industrial waste through leaching behavior, but exclusively using a leaching test, mostly the TCLP [38][39][40][41][42]. Although geochemical modeling of inorganic waste and stabilized waste has been extensively used, only limited research has determined the chemical species and leaching of oxyanions [32,35,43,44], and only some authors studied the geochemical modeling of FA based geopolymer [23,38,45].…”
Section: Introductionmentioning
confidence: 99%